The impact of research joint ventures on firm performance: an empirical assessment - Ralph Siebert (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
Research and Development Joint Ventures are based on cooperative agreements where firms share the costs and results of a particular research project. While theoretical analysis of research joint ventures on profits, R&D intensity, output and prices is more developed in the existing literature, few empirical investigations exist. This paper gives a first insight into the impact of research joint ventures on firms' profit margins. In addition, it investigates the degree to which different firm variables influence participation in research joint ventures (RJVs). For this purpose, 314 US research joint ventures registered from 1985 to 1992 are considered in the study. 2,923 unique cooperating firms and 13,186 noncooperating firms represent the basic sample. A descriptive comparison of cooperating and noncooperating firms finds that cooperating firms achieve a lower profit margin. In addition to this, larger firms are more likely to form RJV's on average. Regression analyses show that two offsetting effects influence the profit margin and that the R&D investments of cooperating firms have a higher impact on profits. Beyond that, the firm size has a positive and significant influence on RJV participation. – – Forschungs-Joint Ventures beruhen auf Kooperationsvereinbarungen, bei denen mehrere Unternehmen übereinkommen, Kosten und Nutzen eines bestimmten Forschungsprojekts zu teilen. Während zahlreiche theoretische Untersuchungen über Forschungs-Joint Ventures und deren Auswirkungen auf die Gewinne, die F&E-Intensität, den Output und die Preise vorliegen, mangelt es an einschlägigen empirischen Analysen. In dieser empirische Untersuchung, die sich auf nordamerikanische Daten stützt, wird analysiert, welche Faktoren Unternehmen veranlassen sich an Forschungs-Joint Ventures zu beteiligen und wie sich dies auf ihre Umsatzrentabilität auswirkt. Einbezogen werden 314 nordamerikanische Forschungs-Joint Ventures, die in der Zeit von 1985 bis 1992 ihre Kooperation angemeldet haben. 2923 unterschiedliche kooperierende Unternehmen und 13186 nichtkooperierende Unternehmen stellen die Grundgesamtheit der Auswahl dar. Ein deskriptiver Vergleich der beiden Unternehmensgruppen zeigt, daß kooperierende Unternehmen eine niedrigere Umsatzrentabilität erzielen. Im Durchschnitt nehmen eher große Unternehmen an einem Forschungs-Joint Venture teil. Regresssionsanalysen zeigen, daß zwei gegeneinander wirkende Effekte die Umsatzrentabilität beeinflussen. Die F&E-Investitionen der kooperierenden Unternehmen besitzen einen größeren Einfluß auf die Profite. Darüber hinaus übt die Unternehmensgröße einen positiven und signifikanten Einfluß auf die Teilnahme an Forschungs-Joint Ventures aus.
Keywords: 330